2013
DOI: 10.1016/j.quascirev.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Multiple tree-ring chronologies (ring width, δ13C and δ18O) reveal dry and rainy season signals of rainfall in Indonesia

Abstract: Climatic hazards, such as severe droughts and floods, affect extensive areas across monsoon Asia and can have profound impacts on the populations of that region. The area surrounding Indonesia, including large portions of the eastern Indian Ocean and Java Sea, plays a key role in the global climate system because of the enormous heat and moisture exchange that occurs between the ocean and atmosphere there. Here, we evaluate the influence of rainfall variability on multiple treering parameters of teak (Tectona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
106
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 58 publications
(76 reference statements)
12
106
3
Order By: Relevance
“…The according TRW chronology dates back to AD 1714. This δ 18 O TR chronology and its dendroclimatological potential as a rainfall indicator has been described in detail in Schollaen et al (2013). Indonesia receives significant rainfall year-round but experiences a distinct wet and dry season.…”
Section: Proxy Data and Site Descriptionmentioning
confidence: 95%
See 2 more Smart Citations
“…The according TRW chronology dates back to AD 1714. This δ 18 O TR chronology and its dendroclimatological potential as a rainfall indicator has been described in detail in Schollaen et al (2013). Indonesia receives significant rainfall year-round but experiences a distinct wet and dry season.…”
Section: Proxy Data and Site Descriptionmentioning
confidence: 95%
“…In previous studies we investigated relationships between seasonal rainfall variability and tree-ring stable isotope records from Javanese teak trees on inter-to intra-annual timescales (Schollaen et al, 2013(Schollaen et al, , 2014. In this study we explore the signal strength of ENSO flavors in our annually resolved δ 18 O TR record from Java, the only well replicated, centennial δ 18 O record from Javanese teak in existence.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sano et al (2010) concluded that the tree ring δ 18 O of Abies spectabilis is more sensitive to rainfall than is ring width or density, because δ 18 O is usually unaffected by a tree's internal factors (Ramesh et al, 1985). The oxygen isotopic ratio of tree-ring alpha-cellulose can be a proxy for paleoclimate reconstruction in areas where little correlation is found between tree-ring widths and climatic factors (e.g., Lipp et al, 1991;Saurer et al, 1995;Robertson et al, 1997;Waterhouse et al, 2002;Rinne et al, 2005;Schollaen et al, 2013). Continuous paleoclimate data in tropical areas that drive the global climate system can be obtained from tropical trees forming annual growth rings or even lacking annual rings, based on high-resolution δ 18 O measurements (e.g., Poussart et al, 2004;Evans and Schrag, 2004).…”
mentioning
confidence: 99%
“…To date, a large number of studies on tropical tree ring formation have been carried out in many regions of the world and on a huge number of tree species [10]. Recent tree ring studies on Java concentrated on the potential of teak chronologies for climate reconstruction [11][12][13][14]. These studies were based on the fact that tree rings are a consequence of seasonally varying precipitation patterns with annually occurring dry seasons.…”
Section: Introductionmentioning
confidence: 99%